Sutura manual em cólon comparando os acessos laparoscópico e laparotômico: estudo experimental em cães - Regadas, Sthela Maria Murad (1999)
The aim of this study is to experimentally develop a technique of laparoscopic hand-sewn endosuture, as compared to the conventional method. Twenty-eight male dogs weighing an average of 16 kg. were operated on. They were divided into two groups with 14 animals each. Group I comprised animals operated on by the conventional method, while those in Group II were laparoscopically approached. Each of such groups was further divided into two ones, each comprising seven animals. Those belonging to Group A were sacrificed on the 7th postoperative day and those belonging to Group B were sacrified on the 14th postoperative day. General anesthesia was performed without endo-tracheal intubation. The sigmoid colon was severed with scissors to the extent of 45% of its diameter, followed by extramucosa, one-layer polydioxanona 000 (PDS®) suture. Suture evaluation was undertaken through macroscopic analysis, sutures tension test and qualitative histologic test carried out by two pathologists. The mean operative time for conventional procedures was 25,3 minutes, while the laparoscopic group required 36,4 minutes. No postoperative complications ensued. Sutures in both groups were intact. The mean pressure obtained by the suture tension test was 222,86 mmHg in animals of both groups, without any no suture rupture. Histologic analysis showed a more extensive inflammatory response in the conventional group; as for the laparoscopic one, inflammation was restricted to the serosa and the external muscular layers. No statistical test was required on account of the similarity of results concerning to suture’s integrity and complications. Nonetheless, Levene’s test was used to verify animals’ weight, t-Student test compared the mean operative time and Kruskal-Wallis test verified the similar results of suture’s tension test. One thus concludes that laparoscopic hand-sewn endosuture is a feasible alternative, yielding the same results obtained in the conventional group as far as the efficacy and the safety of the technique are concerned. This alternative procedure also produces a less inflammatory response. An intensive training in experimental animals is nonetheless required.